2012
DOI: 10.1186/1471-2393-12-93
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of and socio-biologic risk factors for spontaneous preterm birth in HIV positive Nigerian women

Abstract: BackgroundRecent studies have identified HIV as a leading contributor to preterm delivery and its associated morbidity and mortality. However little or no information exists in our sub-region on this subject. Identifying the factors associated with preterm delivery in HIV positive women in our country and sub-region will not only prevent mother to child transmission of HIV virus but will also reduce the morbidity and mortality associated with prematurity and low birth weight. This study was designed to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 22 publications
4
22
2
Order By: Relevance
“…Low socioeconomic class and level of education did not show significant statistical relationship to preterm births. These findings compare favorably with previous studies 4,26 but vary from the report of Ezechi 5 and Omole-Ohonsi 6 where education and socioeconomic class showed significant association with preterm delivery. The decision to seek for healthcare including obstetric care is believed to be easier for the more educated patient and patients in the higher socioeconomic cadre.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Low socioeconomic class and level of education did not show significant statistical relationship to preterm births. These findings compare favorably with previous studies 4,26 but vary from the report of Ezechi 5 and Omole-Ohonsi 6 where education and socioeconomic class showed significant association with preterm delivery. The decision to seek for healthcare including obstetric care is believed to be easier for the more educated patient and patients in the higher socioeconomic cadre.…”
Section: Discussionsupporting
confidence: 85%
“…The reported incidence of preterm birth varies between 5.8% and 11.1% in Nigeria. [3][4][5][6] Preterm birth is the leading cause of perinatal morbidity and mortality worldwide. 7 Despite the fact that global perinatal mortality rates have been on the decline in the last decade, the decline is less prominent in sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 It is worth noting that, in our study, HIV-positive women not on ART or ARV prophylaxis significantly delivered babies with birthweight < 1 000 g. The findings in our study could be due to the fact that the HIV-positive mothers not on ART might have had a lower CD4 cell count and higher HIV RNA viral load, which might have contributed to extremely LBW (< 1 000 g) babies. 18 In our study, 35% of the HIV-positive pregnant women delivered preterm babies, which is higher than the 11% reported in Nigeria 19,20 and 25% in India. 16 The reason for the high premature birth rate in our study is unclear, but it could be related to young age, low education levels, no or low pregnancy weight gain and HIV disease stage 2 or more.…”
Section: Discussioncontrasting
confidence: 49%
“…OALib Journal were preterm delivery rate [18]. Another previous study from US in 1990's found that 19% infants born to HIV-infected mothers were premature [19].…”
Section: /11mentioning
confidence: 99%